Targeted quantitative profiling of metabolites and gene transcripts associated with 4-aminobutyrate (GABA) in apple fruit stored under multiple abiotic stresses. Issue 1 (December 2018) - Brikis, Carolyne; Zarei, Adel; Chiu, Greta; Deyman, Kristen; Liu, Jingyun; Trobacher, Christopher; Hoover, Gordon; Subedi, Sanjeena; DeEll, Jennifer; Bozzo, Gale; Shelp, Barry
Abstract 4-Aminobutyrate accumulates in plants under abiotic stress. Here, targeted quantitative profiling of metabolites and transcripts was conducted to monitor glutamate- and polyamine-derived 4-aminobutyrate production and its subsequent catabolism to succinate or 4-hydroxybutyrate in apple (Malus xdomestica Borkh.) fruit stored at 0 °C with 2.5 kPa O2 and 0.03 or 5 kPa CO2 for 16 weeks. Low-temperature-induced protein hydrolysis appeared to be responsible for the enhanced availability of amino acids during early storage, and the resulting higher glutamate level stimulated 4-aminobutyrate levels more than polyamines. Elevated CO2 increased the levels of polyamines, as well as succinate and 4-hydroxybutyrate, during early storage, and 4-aminobutyrate and 4-hydroxybutyrate over the longer term. Expression of all of the genes likely involved in 4-aminobutyrate metabolism from glutamate/polyamines to succinate/4-hydroxybutyrate was induced in a co-ordinated manner. CO2 -regulated expression of appleGLUTAMATE DECARBOXYLASE 2, AMINE OXIDASE 1, ALDEHYDE DEHYDROGENASE 10A8 andPOLYAMINE OXIDASE 2 was evident with longer term storage. Evidence suggested that respiratory activities were restricted by the elevated CO2 /O2 environment, and that decreasing NAD+ availability and increasing NADPH and NADPH/NADP+, respectively, played key roles in the regulation of succinate and 4-hydroxybutyate accumulation. Together, these findings suggest that both transcriptional and biochemical mechanisms are associated with 4-aminobutyrate and 4-hydroxybutyrate metabolism in apple fruit stored under multiple abiotic stresses. Fruit storage: Biochemical effects in apples The low temperature, reduced oxygen and elevated carbon dioxide conditions under which harvested apples are often stored to delay ripening causes changes in gene activity and metabolism associated with the amino acid 4-aminobutyrate. The effect of these storage conditions, which expose the fruit to a state known as abiotic stress, has not previously been studied in detail. Researchers in Canada and the US, led by Barry Shelp at the University of Guelph in Ontario, studied Empire apples stored in the typical artificial storage conditions for up to 16 weeks. They identified several genes whose activity increased during the study period. These changes were accompanied by increased breakdown of proteins in the fruit, the accumulation of 4-aminobutyrate and altered levels of several other related biochemicals. Understanding these biochemical responses may help optimize fruit storage procedures.